Pembinaan Kemandirian Keuangan Melalui Bisnis Syariah di Lingkungan Lembaga Pendidikan Islam - Muhammad Naufal Baehaki; Kurnia Syiffa’ul Husna; Abdillah Agung Himayanta; Suriagiri Suriagiri; Nur Effendi (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the development of financial independence through sharia-based business practices within Islamic educational institutions. The background of this research is rooted in the increasing need for financial sustainability in educational institutions, particularly those relying heavily on external funding sources. A literature review method is employed, utilizing both primary sources such as peer-reviewed journals and secondary sources including books and institutional reports. The findings indicate that sharia business models not only provide financial support but also instill entrepreneurial values, ethical awareness, and practical skills among students. Moreover, the integration of Islamic economic principles such as fairness, transparency, and prohibition of riba strengthens institutional credibility and community trust. However, challenges remain in terms of managerial capacity, innovation, and market competitiveness. This study concludes that financial independence in Islamic educational institutions can be effectively achieved through structured and sustainable sharia-based business initiatives, supported by strategic planning and stakeholder collaboration.